1996
DOI: 10.3758/bf03205483
|View full text |Cite
|
Sign up to set email alerts
|

The horizon-ratio relation as information for relative size in pictures

Abstract: The horizon-ratio relation was found to be an effective source of information for relative size in pictures under some conditions: when the difference in image size of depicted "same real size" objects was not too great (Experiment 1), and when the horizon line was not too high or too low in the picture (Experiment 2). The latter fmding seemed to be linked to the observers' identification of the horizontal line as the horizon (and not as the edge of a finite surface). In addition, individual patterns of respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0
5

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 24 publications
2
22
0
5
Order By: Relevance
“…First, such pictures may lack spatial information that would be invariant over change of viewpoint of the picture viewer. Other researchers (e.g., Rogers, 1996;Sedgwick, 1991) have suggested that this invariant information, which would normally be used in perceiving real scenes and realistic pictures, is the basis of the robustness of pictures. Second, distortions might be most easily registered with pictures of rectilinear objects because of their regularity; at the same time, these pictures contain the most explicit geometric information NOTES I.…”
Section: Discussionmentioning
confidence: 99%
“…First, such pictures may lack spatial information that would be invariant over change of viewpoint of the picture viewer. Other researchers (e.g., Rogers, 1996;Sedgwick, 1991) have suggested that this invariant information, which would normally be used in perceiving real scenes and realistic pictures, is the basis of the robustness of pictures. Second, distortions might be most easily registered with pictures of rectilinear objects because of their regularity; at the same time, these pictures contain the most explicit geometric information NOTES I.…”
Section: Discussionmentioning
confidence: 99%
“…With this strategy, observers do not compute horizon ratios at all but only attend to the relative HIVFs ofthe tops of objects around eye level. If observers in our experiments did use this strategy, one might wonder whether observers would use the horizon ratio if an explicit horizon were available, given that observers use the horizon ratio to judge relative size in pictures (Rogers, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Its role in apparent-size perception has been less clear. Studies manipulating EH in pictures have produced both strong (Rogers, 1996) and weak (Bingham, 1993) effects for judgments of relative object size. Empirical manipulations of EH in real scenes have also produced ambiguous results for judgments of absolute size (Stoper, 1990;Stoper & Bautista, 1992;Wraga & Neisser, 1995).…”
mentioning
confidence: 99%